Diversity of fish species in inland water of Hochiminh city and new records for fish fauna of Vietnam - Dong, Nguyen Xuan (Academia Journal of Biology, 2013)
The study was carried out from June 2009 to June 2012, there were approximately 1200 fish specimens collected in inland water in Hochiminh city. This paper reports 215 fish species belonging to 65 families of 18 orders. The Perciformes was shown as the most diverse order, with 76 species (35.35% of total species); the Siluriformes order comprises 39 species (18.14%); the carps order (Cypriniformes) consists of 37 species (17.21%); and the other orders consist of from one to twelve species (in the range of 0.47-5.58%). Of the total 215 life-forms of fishes, there were 207 species identified, the rest of 8 life-forms may be a new record for the fish fauna of Vietnam or new ones for science. Additionally, 8 species were considered as threaten species of the Vietnamese Red list (2007), 3 species added for the Vietnamese Red list. The paper also reports 75 species that was considered as species of high economic value, 86 migratory species and 15 species rarely observed in the Sai Gon-Dong Nai river system.